Norovirus GII.4 Sydney 2012 in Italy - Giovanni Maurizio Giammanco (Microbiologia Medica, 2014)
In the 2012-2013 winter season, global surveillance for norovirus circulation evidenced the onset of a new norovirus GII.4 variant, termed Sydney 2012. In Italy, ISGEV hospital-based surveillance revealed that this variant already circulated at low frequency in the winter season 2011-2012 and emerged definitively only in the late 2012. This lag-time pattern mirrors the findings reported elsewhere and suggests that the novel variant circulated at low prevalence before spreading globally.